Bioreproduktif dan Distribusi Ukuran Populasi dalam Menentukan Ukuran Layak Tangkap Ikan Tembang (Sardinella fimbriata Valenciennes, 1847) dari Perairan Selat Makassar - Wayan Kantun; Amel Bitti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
The intensive fishing of Fringescale sardinella the waters around Makassar has led to suspicions of a decline in catchable size. This study aims to analyze the size at first gonad maturity as a basis for determining catchable size. The research was conducted from October to December 2025 at the Beba Fish Landing Ground, Takalar Regency, using a quantitative approach through a survey method to obtain biological data. The results showed that the total length of the Fringescale sardinella caught ranged from 10 to 14.5 cm (12.029 ± 0.926 cm). Analysis of gonad maturity showed that the size at first gonad maturity (Lm) for female Fringescale sardinella was 12.66 cm, while for males it was 13.02 cm. The combined average Lm was 12.89 cm. Meanwhile, the average size of fish caught during the study reached 12.09 cm, lower than the overall gonad maturity size of 13.02 cm. The comparison between catch size and gonad maturity size indicates that most fish caught were below reproductive size. This condition indicates that the majority of individuals in the population were not optimally contributing to the natural spawning process when caught. Catching mackerel at this size cannot be categorized as suitable for fishing and has the potential to disrupt stock sustainability. These results emphasize the importance of setting minimum catch sizes and monitoring exploitation intensity to maintain population balance and support sustainable fisheries management